Trends in aggressive play and refereeing among the top five European soccer leagues - Sapp, R. M.; Spangenburg, E. E.; Hagberg, J. M. (Journal of Sports Sciences, 2018)
Current trends suggest professional soccer is becoming less aggressive, with England often argued to have the most aggressive of the top European leagues. The purpose of this study was to investigate differences in fouls and cards as indicators of aggressive play in the first divisions of England, France, Germany, Italy, and Spain over the past decade. Number of fouls per match and per yellow card has decreased in all leagues since 2007/08, though attempted tackles per foul has not changed or has increased. A lack of substantial rule changes suggests players have become less aggressive in tackling as opposed to referees becoming more lenient. Total number of fouls and cards per match were consistently lower in the English Premier League, however attempted tackles per foul was higher. The data also demonstrate the notions of home advantage and potentially referee bias, since referees tended to call more fouls and award more cards to away teams. Lastly, number of attempted tackles per foul and yellow cards received exhibited the strongest correlations with final league position across the leagues. In conclusion, our data support that elite European soccer has become less aggressive and the English Premier League is the most aggressive league.